Early detection of inflammation-prone STEMI patients using the CRP Troponin Test (CTT). (3rd October 2022) - Brzezinski, R Y; Melloul, A; Berliner, S; Goldiner, I; Stark, M; Rogowski, O; Banai, S; Shenhar-Tsarfaty, S; Shacham, Y
Abstract: Background: Elevated concentrations of C-reactive protein (CRP) early after acute coronary syndrome (ACS) may reflect the magnitude of the inflammatory response to myocardial damage and are associated with worse outcome. However, the routine measurement of both CRP and cardiac troponin simultaneously in the setting of ST segment myocardial infarction (STEMI) is not used broadly. Here, we sought to identify and characterize individuals who are prone to an elevated inflammatory response following STEMI using the CRP Troponin test (CTT) and determine their short- and long-term outcome. Material and methods: We retrospectively examined 1, 186 patients with the diagnosis of acute STEMI, who had at least two successive measurements of combined CRP and cardiac troponin (up to 6 hours apart), all within the first 48 hours of admission. We used Chi-Square Automatic Interaction Detector (CHAID) tree analysis to determine which parameters, timing (baseline vs. serial measurements), and cut-offs should be used to predict mortality. Results: Patients with high CRP concentrations (above 90th percentile, >33mg/L) had higher 30 day- and all-cause mortality rates regardless of their troponin test status (above or below 118, 000 ng/L); 14.4% vs 2.7%, p<0.01. Furthermore, patients with both high CRP and high Troponin levels on their second measurement had the highest 30-day mortality rates compared to the rest of the cohort; 21.4% vs. 3.7%, p<0.01. These patients also had the highest all-cause mortality rates after a median follow up of 4.5 years compared to the rest of the cohort; 42.9% vs 12.7%, p<0.01 (Figure 1). Conclusions: In conclusion, serial measurements of both CRP and cardiac troponin might detect patients at increased risk for short-and long-term mortality following STEMI. We suggest the future use of the combined CRP Troponin-test (CTT) as a potential early marker for inflammatory-prone patients with worse outcomes following ACS. This sub-type of patients might benefit from early anti-inflammatory therapy such as colchicine and anti-IL-1β agents. Funding Acknowledgement: Type of funding sources: None.